Redefining Ḥifẓ al-Dīn as the Basis of Religious Moderation - Maskur Rosyid; Nisrina Khairunnisa (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2022)
A proper understanding of ḥifẓ al-dīn will lead to a moderate mindset. Meanwhile, intolerance occurs due to a complete understanding of religion and considering the truth to only belong to one group. Contemporary scholars interpret ḥifẓ al-dīn as freedom of religion and belief. Through literature study, this article discusses contextualizing the meaning of ḥifẓ al-dīn and its relation to religious moderation in Indonesia. This paper finds that ritualist and radical religious expressions contradict the concepts of harmony and freedom in choosing beliefs as mandated by law.